2021
DOI: 10.1136/bmjresp-2020-000857
|View full text |Cite|
|
Sign up to set email alerts
|

Association between influenza vaccination and hospitalisation or all-cause mortality in people with COVID-19: a retrospective cohort study

Abstract: IntroductionRecent evidence suggests that influenza vaccination may offer protection against COVID-19 severity. Our aim was to quantify the association between influenza vaccination status and risk of hospitalisation or all-cause mortality in people diagnosed with COVID-19.MethodsA retrospective cohort study using routinely collected health records from patients registered to a General Practitioner (GP) practice in South West England within the Electronic Care and Health Information Analytics database. The coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 38 publications
5
48
0
4
Order By: Relevance
“…Among the 41 articles assessed based on full texts, 25 articles were excluded for lacking specific data or did not meet the inclusion criteria. A total of 16 studies were finally included in the review (12 studies on the association between influenza vaccination and SARS-CoV-2 infection [16,18,[21][22][23][24][25][26][27][28][29][30], 6 on the association between influenza vaccination and COVID-19 clinical outcomes [10,17,22,26,31,32], 2 studies containing data on both the associations [22,26]. Nine of the 12 studies on the association between influenza vaccination and SARS-CoV-2 infection contained adjusted estimates.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Among the 41 articles assessed based on full texts, 25 articles were excluded for lacking specific data or did not meet the inclusion criteria. A total of 16 studies were finally included in the review (12 studies on the association between influenza vaccination and SARS-CoV-2 infection [16,18,[21][22][23][24][25][26][27][28][29][30], 6 on the association between influenza vaccination and COVID-19 clinical outcomes [10,17,22,26,31,32], 2 studies containing data on both the associations [22,26]. Nine of the 12 studies on the association between influenza vaccination and SARS-CoV-2 infection contained adjusted estimates.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…COVID-19 virus has the potential to harm us as we are constantly exposed to the virus while visiting public places like restaurants, retail stores, businesses, places of worship, public parks and gardens, and places of work. Exposure to the virus can trigger our immune system to react to the virus as it has high negative outcomes toward our body, which has led to intense research and human clinical studies about effective COVID-19 vaccination [20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In the survey study, the respondents were shown how previous participants have answered survey questions in their country regarding behavioral perception about COVID-19 pandemic; vaccination drive; social distancing; preventive measures like wearing masks, hand washing, using sanitizers, etc. [15,[22][23][24][25][26][27][28]. The information to the respondents was provided in a randomized way during the survey which showed the descriptive norms of the respondents about acceptance of the vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations